Investigation of powdery mildew disease in various oak (Quercus) trees; a case study from Istanbul/Turkey - (:unkn) unknown (Parlar Scientific Publications, 2020)
Oak tree, with its different varieties, grows in almost all regions of Turkey. It is one of the wood materials valued for its timber. This noble tree is affected by powdery mildew (PM) disease, especially at its young ages. PM is a fungal disease infecting wide range of plant species as well as oak trees. It is quite harmful to nurseries, groves and coppice forests, and it reduces the quality and quantity of byproducts. In this study, PM disease, its formation and spread conditions were investigated in various oak species populated in six different districts of Istanbul. Field observations, diagnostic and laboratory studies revealed that oak species type, its neighboring communities, population density, topographical features of the area, operating mode, and climatic conditions such as temperature, relative humidity, wind and airing have determinative affects in PM disease development and dispersal. Thus, findings of this study will become valuable source for further physiological and molecular studies, as well as they will give insight to authorities in terms of protection of oak species from this damaging disease. © by PSP.
Keywords: Coppice; Grove; Powdery mildew; Quercus; Topography